The fifth influenza A(H7N9) epidemic: A family cluster of infection in Suzhou city of China, 2016. (September 2018) - Wang, Jiajia; Su, Nan; Dong, Zefeng; Liu, Cheng; Cui, Pengwei; Huang, Jian-an; Chen, Cheng; Zhu, Yehan; Chen, Liling
Abstract: Objective: Influenza A(H7N9) virus is known for its high pathogenicity in human. A family cluster of influenza A(H7N9) virus infection was identified in Suzhou, China. This study aimed to investigate the possibility of human-to-human transmission of the virus and examine the virologic features of this family cluster. Methods: The clinical and epidemiologic data of two patients in the family cluster of influenza A(H7N9) virus infection were collected. Viral RNA in samples derived from the two patients, their close contacts, and the environments with likely influenza A(H7N9) virus transmission were tested by real-time reverse transcriptase polymerase chain reaction (rRT-PCR) assay. Hemagglutination inhibition (HI) assay was used to detect virus-specific antibodies. Genetic sequencing and phylogenetic analysis were also performed. Results: The index patient (Case 1), a 66-year old man, was virologically diagnosed with influenza A(H7N9) virus infection 12 days after experiencing influenza-like symptoms, then died of multi-organ failure. His 39-year old daughter (Case 2), denying any other exposure to influenza A(H7N9) virus, became infected with influenza A(H7N9) virus following taking care of her father during his illness. Sequencing viral genomes isolated from the two patients showed nearly identical nucleotide sequence, and genetically resembled the viral genome isolated from a chicken in the wet market where the index patient once visited. All three influenza A(H7N9) viruses shared S138A, G186V, Q226L mutations in HA (H3) protein and a single basic amino acid (PEIPKGR↓G) at the cleavage site. Conclusions: Human-to-human transmission of influenza A(H7N9) virus most likely occurred in this household. The three-amino-acid mutations in HA protein were discovered in this study, which might have increased the binding affinity of influenza A(H7N9) virus to the receptor on trachea epithelial cells to facilitate viral transmission among humans.